(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
The different parameters on physico-chemical characteristics especially the free fatty acid (FFA), peroxide values, iodine values, lipid class composition and major elements of shrimp head waste were studied. The oil was fractionated into mono, di and triglycerides by silicic acid column chromatography. The calcium ranged from 3.26mg/100 gm to 5.08 mg/100 gm, magnesium 4.79mg/100gm to 7.02 mg/100gm, sodium 51.09 mg/100gm to 73.05 mg/100gm and potassium 52.91 mg/100gm to 83.07 mg/100gm respectively. The percentage of crude protein is 49.47. Bangladesh J. Sci. Ind. Res. 41(1-2), 63-66, 2006